Nanostructured Al doped SnO 2 films grown onto ito substrate via spray pyrolysis route - Benhaliliba, M.; Benouis, C.E.; Ocak, Y.S.; Yakuphanoğlu, Fahrettin (My University, 2012)
We report on nanostructured films of Al doped tin oxide grown by facile spray pyrolysis route, and their physical properties were investigated. The sprayed films were grown onto indium tin oxide (ITO) substrate at 300 °C from the precursor (SnCl 4, 5H 2O). The content of Al is kept at 3 % in the solution. Structural, optical, electrical and surface properties were investigated. X-rays pattern reveals polycrystalline structure and SnO 2 phase occurence. The visible transmitance exceeds 85 %, the band gap is found to be 3.7 eV. Nanotips were observed by 3D atomic force microscope (AFM) observation. Using the Hall effect measurements system (HMS), the films exhibit very low resistivity found to be 9.85 10 - 5 ? cm, a high electron concentration is around 10 21 cm - 3, and the mobility reaches the value of 20 cm 2/Vs. © 2012 Sumy State University.
Keywords: Al doped tin oxide; Hall measurement; ITO substrate; Nanostructured films; Sprayed films; Transmittance